The effectiveness of student development program (sdp) modules for UiTM students at Pahang Campus / Juliza Iskan, Nor Fazlinda Mahtar @ Mohtar and Wan Norhayani Che Wan Khirudin - Iskan, Juliza; Mahtar @ Mohtar, Nor Fazlinda; Che Wan Khirudin, Norhayani (2011)
Bernd Schulz (2008) stated that soft skills are shaping human beings personalities. Therefore, to face the obstacles and challenges, UiTM has taken initiative to prepare the student with soft skills abilities by providing such programs for instance, the Student Development Program (SDP), "Program Kemahiran Insaniah" (pro-KI) and Co-curriculum. Therefore, SDP are organized by Department of Student Training, Development and Leadership or well known as ULPKP among UiTM members. This unit was created to implement self-development programs and student leadership in a systematic and coordinated through the residential colleges, faculties, campuses and student unions. UiTM requires all students to attend the SDP at each semester in which they must complete five modules that have been set by the university. Modules they need to attend are the personal development module, the module self-development, leadership and organizational management, strengthening self-esteem and career strategic and work allocation module. The objective of this study was to find out, whether the Student Development program (SDP) improves students' soft skills at UiTM Pahang. This study was also conducted to determine the effectiveness of SDP that organized by UiTM Pahang to their students. Besides that, the purposes of this study was find out which module in SDP is not effective and are the student's soft skills enough to fulfill the employer expectations after attending this program. A questionnaire used as the main instrument and the data was analyzed using SPSS version 18.0. The questionnaires were distributed personally by researchers to the respondents who being choosing by cluster sampling. They are diploma students in part six from Faculty of Applied Science (AS I20), Faculty of Wood Technology (AS117), and Faculty of Agro Technology (ATI to). This study found that, all the modules provided are effective, but the self development modules and self-growth modules get lower frequency of agree which are 22 % only. Then, management need to restructure again the method that they used to ensure it's was relevant with the current situation. Other than that, the facilities provided should be adequate and are in good conditions, such as the LCD and classroom. In addition, the result had also indicated that student's soft skills was improved after they attended all the modules, because each module has its own strength such as effectiveness and organizational management module show that 51.8% of respondents agree with this module can develop and establish leadership style after they are attend this program. Last but not least, students cannot depend only on the SDP to make sure their soft skills meet employer expectations. It is because, SDP that provided by UiTM just a platform to help student's become more independent.